2019
DOI: 10.1038/s41467-019-12644-1
|View full text |Cite
|
Sign up to set email alerts
|

The allotetraploid origin and asymmetrical genome evolution of the common carp Cyprinus carpio

Abstract: Common carp (Cyprinus carpio) is an allotetraploid species derived from recent whole genome duplication and provides a model to study polyploid genome evolution in vertebrates. Here, we generate three chromosome-level reference genomes of C. carpio and compare to related diploid Cyprinid genomes. We identify a Barbinae lineage as potential diploid progenitor of C. carpio and then divide the allotetraploid genome into two subgenomes marked by a distinct genome similarity to the diploid progenitor. We estimate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(151 citation statements)
references
References 68 publications
9
119
1
Order By: Relevance
“…This could lead to uneven ohnolog loss rates, a process that is referred to as biased fractionation [ 27 ]. In line with previous studies on teleosts [ 28 , 29 ], we found significant biases in local gene loss, albeit only in 9 of 47 syntenic duplicate blocks. However, we did not find equivalent large-scale biases in expression loss (Additional file 1 : Figure S9), thus rendering regional differences in selection constraints an unlikely explanation for the large number of ohnologs experiencing loss of expression in one copy.…”
Section: Resultssupporting
confidence: 92%
“…This could lead to uneven ohnolog loss rates, a process that is referred to as biased fractionation [ 27 ]. In line with previous studies on teleosts [ 28 , 29 ], we found significant biases in local gene loss, albeit only in 9 of 47 syntenic duplicate blocks. However, we did not find equivalent large-scale biases in expression loss (Additional file 1 : Figure S9), thus rendering regional differences in selection constraints an unlikely explanation for the large number of ohnologs experiencing loss of expression in one copy.…”
Section: Resultssupporting
confidence: 92%
“…Although Cyprinidae contains more polyploid species than any other vertebrate groups, the origin of polyploidy in cyprinid species is still unknown. C. carpio, the most studied species, is reported to be allotetraploid according to cytogenetic [44] and genomic [25,45] evidence. Tor species in Torini is also speculated to be allotetraploid based on ohnologue genealogy of Sox genes [33].…”
Section: (B) Genetic Basis Of Adaptive Potential In Polyploid Cyprinidaementioning
confidence: 99%
“…Another challenge is that some cyprinid species have experienced genome duplications and polyploidization (Yang et al, 2015). Polyploids usually harbour more complex genome organization and gene content than diploids (Xu et al, 2019).…”
mentioning
confidence: 99%